The three-dimensional reconstruction of the dilated renal pelvicalyceal system by non-enhanced computed tomography - B. G. Guliev; B. K. Komyakov; A. E. Talyshinskiy (Вестник урологии, 2021)
Introduction. The three-dimensional reconstruction of the renal pelvicalyceal system (PCS) is possible when performing enhanced computed tomography (CT). However, the use of a contrast agent has its limitations associated with the presence of allergy and chronic kidney disease.Purpose of the study. To describe the method of semi-autonomous three-dimensional (3D) reconstruction of the PCS based on non-enhanced CT images of patients with upper urinary tract obstruction.Materials and methods. Five patients diagnosed with renal colic were recruited from April-May 2021. All patients underwent CT-urography after informed consent. Medical Imaging Interaction Toolkit program (MITK) expanded with explainable update were used for 3D-reconstruction of PCS via excretory and native phases. To assess the accuracy of the latter, both contrast and non-contrast models were compared regarding their surface area. Also, the PCS of one patient was used to reconstruct virtual endoscopic views based on enhanced and non-enhanced models. Five urologists estimated their similarity and potential use of non-enhanced models for the interventional planning via a Likert scale questionnaire. The resulting models were also analyzed by programmer-engineers to test their suitability for 3D-printing.Results. The average surface area of enhanced and non-enhanced models was 3291 mm2 and 2879 mm2, respectively. Obtained models were suitable for their intraluminal reconstruction and potential 3D-printing. Analyzed properties of non-enhanced models were estimated at 4.5 out of 5.0.Conclusion. The described semi-autonomous reconstruction of the renal PCS based on non-enhanced CT images allows for a short time to reconstruct its 3D-view in patients with the upper urinary tract obstruction.